2017
DOI: 10.1177/1043454217727515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Recommendations Based on an Updated Review of Breast Cancer Risk Among Women Treated for Childhood Cancer

Abstract: Breast cancer is the most common secondary malignancy among women treated for childhood cancer. This review highlights interacting etiologies contributing to development of secondary breast cancer to complement guidelines for surveillance and survivorship care and make recommendations for clinical practice. Treatment exposures determine Children's Oncology Group breast cancer surveillance guidelines; those treated with cumulative doses ≥20 Gy chest irradiation should undergo annual magnetic resonance imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…Risk is highest following chest radiation, anthracyclines, or alkylating agents. At‐risk survivors should be managed according to the Children's Oncology Group breast cancer surveillance guidelines …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk is highest following chest radiation, anthracyclines, or alkylating agents. At‐risk survivors should be managed according to the Children's Oncology Group breast cancer surveillance guidelines …”
Section: Discussionmentioning
confidence: 99%
“…At-risk survivors should be managed according to the Children's Oncology Group breast cancer surveillance guidelines. 73 Contralateral breast cancer is the most common second malignancy by far in survivors of primary breast cancer, 74 and risk increases with younger age at diagnosis. Compared with women whose primary diagnosis occurred at age 40+, women initially diagnosed with breast cancer at age 29 or younger have an HR of 2.8 for the development of contralateral breast cancer.…”
Section: Second Malignanciesmentioning
confidence: 99%
“…Compared to sporadic breast cancer, breast cancer after radiotherapy was more likely to be bilateral (6%-34%), to have negative hormone receptors (27%-49%), and to be high-grade (35%). Disease-free survival has been shown to be similar to groups of patients with primary breast cancer of the same immunohistochemical profile, although comorbidities are greater in the groups of patients who received previous radiation therapy, probably due to the effects of the initial treatment 11 . Due to the risk of bilateral breast cancer, the recommended treatment is a bilateral mastectomy, as performed in the case analyzed in this study.…”
Section: Discussionmentioning
confidence: 97%
“…In a systematic review, published in 2018, it is suggested that mammography and MRI screenings be performed starting at the age of 25 or after eight years of initial radiotherapy (whichever comes first) in women who received> 20 Gy in the chest wall before turning 30 years old 10,11 . Other authors already recommend the practice for groups that received > 10 Gy in the chest wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation